2010
DOI: 10.1136/jmg.2008.060913
|View full text |Cite
|
Sign up to set email alerts
|

Polyalanine expansion in the ZIC3 gene leading to X-linked heterotaxy with VACTERL association: a new polyalanine disorder?

Abstract: It is hypothesized that this novel and de novo polyalanine expansion in ZIC3 contributes to the VACTERL association in this patient. A newborn male is described with features of the VACTERL association, including anal atresia, laryngeal and oesophageal atresia with tracheo-oesophageal fistula, dextroposition of the heart with persistent left superior vena cava, and unilateral multicystic kidney. As the clinical picture of the VACTERL association overlaps with X-linked heterotaxy caused by ZIC3 mutations, the Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 33 publications
5
57
0
Order By: Relevance
“…In particular, the ZIC3 p.(Ala55dup) variant was reported earlier in a series of heterotaxy cases 9,10 and a variant with an expansion of two alanine residues was reported in a case of VACTERL association. 11 However, the presence of an expansion of one alanine in 5% the American population casts serious doubt on its causality in any defect. We considered the classical large duplication in 22q11 as causal for the CHD in families MC074 and MC089 although with incomplete penetrance.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the ZIC3 p.(Ala55dup) variant was reported earlier in a series of heterotaxy cases 9,10 and a variant with an expansion of two alanine residues was reported in a case of VACTERL association. 11 However, the presence of an expansion of one alanine in 5% the American population casts serious doubt on its causality in any defect. We considered the classical large duplication in 22q11 as causal for the CHD in families MC074 and MC089 although with incomplete penetrance.…”
Section: Discussionmentioning
confidence: 99%
“…One exception is the report of a missense mutation in ZIC3 , an X-linked gene associated with heterotaxy, in a patient who had all of the VACTERL malformations and whose cousin and a nephew had cardiovascular anomalies [Ware et al, 2004]. ZIC3 deletion or mutation has been reported in 2 other males who met criteria for VACTERL association [Wessels et al, 2010;Chung et al, 2011].…”
Section: Single Gene Mutations Among Conditions With Component Malformentioning
confidence: 99%
“…All have previously been described to be associated with ciliary dyskinesia in either mice or humans, and in some cases both. 16,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] We find it of significance, therefore, that a large proportion of affected genes are associated with not only isomerism, but also with ciliary dyskinesia. Previous studies have shown that over 40% of patients with isomerism also have ciliary dyskinesia.…”
Section: Discussionmentioning
confidence: 78%